Biosynthesis of copper nanoparticles using methanol extract of sugar-apple leaves (Anonnaceae squamosa), and its antioxidant activity. Issue 1 (1st February 2022) - Maulana, I; Fasya, D; Ginting, B; Efendi, R
Abstract: Study on the biosynthesis of copper nanoparticles has been carried out employing the green synthesis method using methanol extract of Sugar-Apple leaf ( Anonnaceae squamosa ) as a reducing agent and stabilizer. The results of the reduction reaction of Cu 2+ ions were confirmed using a UV-Vis Spectrophotometer, Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM). The results of the characterization analysis showed that the nanoparticles formed were Cu, CuO2, Cu2 O, and CuO, with crystal size of 38.17 nm, 27.82 nm, 15.59 nm, and 37.08 nm respectively. The obtained copper nanoparticles were tested for their antioxidant activity using the 1, 1-diphenyl-2-picrihydrazil (DPPH) method. The antioxidant test results from the formed copper nanoparticles showed an IC50 value of 263.35 ppm, while vitamin C was 5.81 ppm. The previous study on the antioxidant activity of the methanol extract of Sugar-Apple leaf showed an IC50 value of 5.6 ppm. Therefore, it can be concluded that the antioxidant activity of the formed nanoparticles has a weak inhibitory power against 1, 1-diphenyl-2-pycrilhydrazil (DPPH) radicals.